Charting a path toward combination therapy for Alzheimer's disease. (January 2014) - Stephenson, Diane; Perry, Dan; Bens, Cynthia; Bain, Lisa J; Berry, Donald; Krams, Michael; Sperling, Reisa; Dilts, David; Luthman, Johan; Hanna, Debra; McKew, John; Temple, Robert; et al.
<x xml:space="preserve">Abstract</x> It is acknowledged that progress in combined therapeutic approaches for Alzheimer's disease (AD) will require an unprecedented level of collaboration. At a meeting co-hosted by the Accelerate Cure/Treatments for Alzheimer's Disease Coalition and the Critical Path Institute, investigators from industry, academia and regulatory agencies agreed on the need for combinatorial approaches to treating AD. The need for advancing multiple targets includes recognition for novel adaptive trial designs that incorporate existing and new biomarkers to evaluate drug effects independently and in combination. A combination trial now being planned may test drugs targeting different pathogenic pathways or multiple targets along a common pathway. Collaborations and consortia-based strategies are pivotal for success and a regulatory framework is recommended for success.